ANALISIS POTENSI SEKTOR EKONOMI DALAM UPAYA PENINGKATAN PERTUMBUHAN EKONOMI SEKTORAL KABUPATEN LOMBOK TENGAH TAHUN 2017-2021 - Mohadi; Aminy, Muhammad Habibullah (Fakultas Ekonomi dan Bisnis Universitas Islam Al-Azhar Mataram, 2023)
This research is entitled Analysis of the Potential of the Economic Sector in Efforts to Increase Sectoral Economic Growth in Central Lombok Regency in 2017-2021. In this study, researchers wanted to see which sectors have the potential to be developed in Central Lombok Regency based on LQ (Location Quotients) analysis. The type of this research is quantitative research with a descriptive approach. The analytical tool used in this study is to use LQ analysis. The results of this study are based on the analysis of the potential LQ sectors, namely the agricultural sector with an average LQ value of 1.16, processing industry with an average LQ value of 1.24, construction/building with an average LQ value of 1.1, 41, water supply, waste management, waste and recycling with an average LQ value of 1.54, transportation and warehousing with an average LQ value of 2.31, real estate with an average LQ value of 1.20, government administration, defense, and social security with an average LQ score of 1.01, health services and social activities with an average LQ score of 1.26 and finally other services with an average LQ score of 1.07. While the most basic sector is the transportation and warehousing sector, with an average LQ value of 2.31.